Decorative crystal balls causing intestinal perforation - Bilal Mirza; Lubna Ijaz; Afzal Sheikh (Wolters Kluwer Medknow Publications, 2011)
Crystal jelly balls are used for decorative purpose in homes and offices. They swell on contact with water. We managed a patient with a clinical diagnosis of acute abdomen. At surgery, there was fecal peritonitis and three ileal perforations caused by previously ingested decorative crystal balls.